A composite expansion agent and its application in concrete
By adopting a composite expansion consisting of a variety of expansion agents, the negative effects of existing expansion agents on concrete work performance and compressive strength are solved, and better infiltration, durability and strength effects are achieved.
Patent Information
- Application Number
- CN202410837356.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-26
AI Technical Summary
When existing expansion agents improve the permeability and durability of concrete, they often have a negative impact on the working performance and compressive strength of concrete, and their performance still needs to be improved.
A composite expansion agent, which is composed of fluoride gypsum, scoring phosphate dihydrogen sodium, white cloudstone, glycerin, calcium sulfate, polyamide, and sodium synthetic silicate. Obtain a expansion agent with a particle size below 100 mesh.
This composite expansion can not only effectively prevent concrete shrinkage, extend the expansion time, achieve stable and long -acting anti -contraction effect, but also improve the working performance and compressive strength of the concrete without affecting the strength of the concrete.
Smart Images

Figure BDA0004913546200000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete additive development, in particular to a composite expansion agent and application thereof in concrete. Background Art
[0002] With the development of society, concrete structures are developing more towards super-high-rise and large-span structures. The application fields of high-strength concrete are increasing, and the pouring volume of concrete is also increasing. Many studies have shown that the shrinkage value of high-strength concrete is related to the water-binder ratio. The lower the water-binder ratio, the greater the total shrinkage value of the concrete, and the higher the ratio of the autogenous shrinkage value to the total ratio, which is prone to early shrinkage cracks. The addition of an appropriate amount of expansion agent can not only significantly reduce the shrinkage of concrete, but also improve the compactness of concrete in a restricted state due to expansion, thereby significantly improving the durability and impermeability of concrete.
[0003] Calcium oxide-calcium sulfoaluminate expansion agents, whose expansion sources are calcium hydroxide and calcium sulfoaluminate, are mainly used to solve the problem of early self-shrinkage of high-strength concrete due to their large early expansion amount, fast expansion rate, and stable expansion performance. Their faster expansion can match the rapidly developing strength of high-strength concrete, and they have been widely used in construction projects. However, high-strength concrete will generate a large amount of hydration heat due to the large amount of cementitious materials used, and concrete is a poor conductor of heat, which leads to a large temperature rise in a short period of time for large volumes of high-strength concrete. High-strength concrete will produce a large amount of temperature drop shrinkage and drying shrinkage in the later stage, but the compensatory effect of calcium oxide-calcium sulfoaluminate expansion agents on temperature shrinkage and drying shrinkage is not significant.
[0004] Magnesium oxide expansion agent, whose expansion source is Mg(OH)2, is rarely used in industrial and civil buildings due to its slow expansion rate, which may cause volume stability problems of concrete. It is mainly used in my country's water conservancy industry to compensate for the temperature drop shrinkage of large-volume concrete in hydraulic engineering. The current standard "Concrete Expansion Agent" does not include it. Compared with other expansion source expansion agents, MgO requires less water for hydration, the physical and chemical properties of the expansion source Mg(OH)2 are stable, and the expansion process can be controlled; and research has found that when the firing temperature is appropriate, the reaction rate of lightly fired MgO is faster, and some people have tried to use it in the industrial and civil construction industry.
[0005] Chinese patent CN107140864A discloses a concrete expansion agent and a preparation method thereof, wherein the raw materials include, by weight: 330-450 parts of bauxite clinker, 500-600 parts of gypsum powder, and 70-80 parts of naphthalene-based high-efficiency water reducer; the above raw materials are mixed to obtain the concrete expansion agent. The concrete expansion agent of the invention can prevent the cracking of large-volume concrete, improve the anti-permeability, have micro-expansion to prevent concrete shrinkage, and can be waterproof, anti-seepage and anti-cracking in engineering construction.
[0006] Chinese patent CN104446117A discloses a concrete expansion agent, which is made of the following raw materials in weight percentage: 35-45% calcium sulfoaluminate, 1-5% magnesium oxide, 18-25% plasticizing water reducer, 16-23% mineral ultrafine powder, 2-7% sodium tripolyphosphate, 5-10% water-retaining material, and 1-5% sodium gluconate. The invention solves the problems of low expansion rate and insufficient shrinkage compensation of existing expansion agents. At the same time, by adding the product to concrete, the strength of the concrete in the middle and late stages is improved and the setting time is appropriately extended. The product also has excellent crack resistance and impermeability, good adaptability, and is suitable for concrete of different strength grades.
[0007] However, the expansion agents in the prior art often have a negative impact on the working performance and compressive strength of concrete, and the performance still needs to be improved. Summary of the invention
[0008] The purpose of the present invention is to provide a composite expansion agent and application thereof in concrete, which can not only prevent concrete shrinkage but also improve the working performance and compressive strength of concrete.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0010] The present invention provides a composite expansion agent, comprising the following components in parts by weight:
[0011] 18-22 parts of fluorgypsum, 8-12 parts of disodium dihydrogen pyrophosphate, 8-12 parts of dolomite, 3-8 parts of monoglyceride, 8-12 parts of calcium sulfoaluminate, 8-12 parts of polyamide and 8-12 parts of sodium silicate pentahydrate.
[0012] Preferably, it is composed of the following components in parts by weight:
[0013] 20 parts of fluorgypsum, 10 parts of disodium dihydrogen pyrophosphate, 10 parts of dolomite, 5 parts of monoglyceride, 10 parts of calcium sulfoaluminate, 10 parts of polyamide and 10 parts of sodium silicate pentahydrate.
[0014] The present invention also provides a method for preparing the composite expansion agent, comprising the following steps:
[0015] All raw materials are mixed and ball-milled to obtain the composite expanding agent.
[0016] Preferably, the particle size of the composite expansion agent is below 100 mesh.
[0017] The invention also provides application of the composite expansion agent as a concrete auxiliary agent.
[0018] Preferably, the concrete additive is used to prevent concrete shrinkage.
[0019] Preferably, the concrete additive is used to improve the working performance and compressive strength of concrete.
[0020] The present invention also provides a concrete comprising the following raw materials in parts by weight:
[0021] 250-350 parts of cement, 1500-2500 parts of aggregate, 35-45 parts of anti-cracking agent, 30-50 parts of water reducing agent, and 3-8 parts of the above-mentioned composite expansion agent.
[0022] Technical effects and advantages of the present invention:
[0023] The present invention adopts multiple expansion source raw materials, specifically adopts 20g of fluorgypsum, 10g of disodium dihydrogen pyrophosphate, 10g of dolomite, 5g of monoglyceride, 10g of calcium sulfoaluminate, 10g of polyamide and 10g of sodium silicate pentahydrate for compound application, and each component can synergistically improve the performance of the expansion agent. The composite expansion agent provided by the present invention can not only effectively prevent the shrinkage of concrete, prolong the expansion time, and achieve a stable and long-lasting anti-shrinkage effect, but also can improve the working performance of concrete compared with the original concrete formula without adding the expansion agent, and will not affect the strength of the concrete, and achieve a better application effect. DETAILED DESCRIPTION
[0024] The present invention provides a composite expansion agent, comprising the following components in parts by weight:
[0025] 18-22 parts of fluorgypsum, 8-12 parts of disodium dihydrogen pyrophosphate, 8-12 parts of dolomite, 3-8 parts of monoglyceride, 8-12 parts of calcium sulfoaluminate, 8-12 parts of polyamide and 8-12 parts of sodium silicate pentahydrate; preferably, it is composed of the following components in parts by weight: 20 parts of fluorgypsum, 10 parts of disodium dihydrogen pyrophosphate, 10 parts of dolomite, 5 parts of monoglyceride, 10 parts of calcium sulfoaluminate, 10 parts of polyamide and 10 parts of sodium silicate pentahydrate.
[0026] The fluorspar of the present invention is a byproduct of preparing hydrogen fluoride from sulfuric acid and fluorspar, and is mainly anhydrous calcium sulfate.
[0027] The disodium dihydrogen pyrophosphate of the present invention has a chemical formula of Na2H2P2O7, and acts as a moisture retaining agent in the present invention, and can delay the expansion effect of other components.
[0028] The chemical composition of the dolomite of the present invention is CaMg(CO3)2, and the crystal belongs to a trigonal carbonate mineral. The crystal structure of dolomite is similar to that of calcite, the crystal shape is a rhombohedron, the crystal face is often bent into a saddle shape, polysynthetic twins are common, and it is mostly in blocky and granular aggregates, belonging to carbonate minerals. In the present invention, it is preferably added to the ball mill in the form of powder.
[0029] The glycerol monoester described in the present invention is a monoester compound synthesized by dehydration condensation of one of the three hydroxyl groups in the glycerol (propylene glycol) molecule by an acid (organic carboxylic acid or phosphoric acid), and it synergizes with other components in the present invention to jointly enhance the composite expansion effect.
[0030] The calcium sulfoaluminate of the present invention can be generated by the reaction of calcium oxide, aluminum oxide and calcium sulfate at 1000-1250° C. It is an early strength mineral and the main component of fast-hardening, expansive and self-stress cement, and is used as an early strength agent, quick setting agent and expansive agent of silicate cement.
[0031] The polyamide described in the present invention is commonly known as nylon, and its English name is Polyamide (PA for short), which is a general term for thermoplastic resins containing repeating amide groups - [NHCO] - on the main chain of the molecule, including aliphatic PA, aliphatic-aromatic PA and aromatic PA; conventional polyacrylamide is preferably used in the present invention.
[0032] The sodium silicate pentahydrate of the present invention has a chemical formula of Na2SiO3·5H2O, is a white crystalline solid, has high solubility, and can be obtained by reacting silicon dioxide and sodium hydroxide.
[0033] Under the premise of the weight proportion provided by the present invention, each component can achieve the best coordination effect, and the expansion is more stable and lasts longer.
[0034] The present invention also provides a method for preparing the composite expansion agent, comprising the following steps: mixing and ball-milling all raw materials to obtain the composite expansion agent; preferably, the particle size of the composite expansion agent is below 100 meshes.
[0035] The present invention also provides the use of the composite expansive agent as a concrete additive; preferably, the concrete additive is used to prevent concrete shrinkage; preferably, the concrete additive is used to simultaneously improve the working performance and compressive strength of concrete.
[0036] The present invention also provides a concrete comprising the following raw materials in parts by weight:
[0037] 250-350 parts of cement, 1500-2500 parts of aggregate, 35-45 parts of anti-cracking agent, 30-50 parts of water reducing agent, and 3-8 parts of the above-mentioned composite expansion agent.
[0038] In the present invention, the aggregate may be, for example, silica, quartz, sand, crushed marble, glass balls, granite, basalt, limestone, sandstone, calcite, marble, serpentine, travertine, dolomite, feldspar, gneiss, fly ash, alluvial sand, any other durable aggregate and mixtures thereof; in the present invention, the aggregate preferably includes river sand, crushed stone and fly ash.
[0039] In the present invention, the concrete may further comprise conventional additives used in the prior art, such as grinding aids, strength enhancers, retarders, mechanical reinforcing materials, stabilizers or thickeners or polymer dispersions in liquid form or solid form (e.g. powder form):
[0040] The grinding aids, such as amines, amino alcohols, glycols, glycol derivatives, glycerol, glycerol derivatives, molasses, corn syrup; the strength enhancer is preferably selected from alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal oxides, alkaline earth metal oxides, alkali metal nitrates, alkaline earth metal nitrates, alkali metal nitrites, alkaline earth metal nitrites, alkali metal thiocyanates, alkaline earth metal thiocyanates, alkali metal halides, alkaline earth metal halides and alkaline earth metal formates;
[0041] The retarder is preferably selected from sucrose, glucose, polymeric sugar and phosphoric acid;
[0042] The mechanical reinforcement material is preferably selected from synthetic polymer fibers (e.g. polypropylene), natural fibers, steel fibers or meshes of these materials;
[0043] The stabilizer or thickener is preferably selected from cellulose ethers and cellulose derivatives, starch, starch ethers and other starch derivatives, xanthan gum, welan gum, dillon gum, high molecular weight polyacrylamide and copolymers thereof containing acrylic acid and / or ATBS;
[0044] The polymer dispersion in liquid form or solid form (e.g. powder form) is preferably selected from polyacrylates, styrene-butadiene copolymers and ethylene-vinyl acetate copolymers;
[0045] In the present invention, the water reducing agent preferably contains tannic acid and sodium xylene sulfonate; in practical applications, if necessary, it can be used in combination with other types of water reducing agents.
[0046] Among water reducers, polycarboxylic acid water reducers include polycarboxylic acid ethers, polycarboxylate / cross-linked polymer composites, polycarboxylate / oriented polymer composites, polycarboxylate / highly modified polymer composites, polyether carboxylic acid polymers, maleic acid copolymers, maleate copolymers, maleic acid derivative copolymers, carboxyl-containing polyethers, sulfone-terminated polycarboxylic acid-containing multi-component polymers, polycarboxylic acid graft copolymers, polycarboxylic acid compounds, and polycarboxylate ether polymers. Melamine water reducers include melamine sulfonic acid-formaldehyde condensates, melamine sulfonate condensates, and melamine sulfonate-polyol condensates. Lignin water reducers include lignin sulfonates and their derivatives.
[0047] In the present invention, the concrete may further comprise conventional air entraining agents used in the prior art, including anionic surfactants, cationic surfactants, nonionic surfactants and amphoteric surfactants; anionic surfactants are preferably selected from carboxylic acid, sulfate, sulfonic acid and phosphate type surfactants; cationic surfactants are preferably selected from amine salt, primary amine salt, secondary amine salt, tertiary amine salt and quaternary ammonium salt type surfactants; nonionic surfactants are preferably selected from ester, ester-ether, ether and alkanolamide type surfactants; amphoteric surfactants are preferably selected from amino acid and sulfobetaine type surfactants.
[0048] In the present invention, the concrete may also contain conventional defoamers used in the prior art, including oxyalkylene, silicone, alcohol, mineral oil, fatty acid and fatty acid ester defoamers; oxyalkylene defoamers are preferably selected from polyoxyalkylenes such as (poly)oxyethylene-(poly)oxypropylene adducts; (poly)oxyalkylene alkyl ethers such as diethylene glycol heptyl ether, polyoxyethylene oleyl ether, polyoxypropylene butyl ether, polyoxyethylene polyoxypropylene 2-ethylhexyl ether, and oxyethylene propylene oxide adducts of higher alcohols having more than 8 carbon atoms or secondary alcohols having 12 to 14 carbon atoms; (poly)oxyalkylene (alkyl) aryl ethers such as polyoxypropylene phenyl ether and polyoxyethylene nonyl phenyl ether; defoamers prepared by oxyalkylene and acetylenic alcohols such as 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,5-dimethyl-3-hexyne-2,5-diol and 3 -acetylenic ethers obtained by addition polymerization of 1-methyl-1-butyn-3-ol; (poly)oxyalkylene fatty acid esters such as diethylene glycol oleate, diethylene glycol laurate and ethylene glycol distearate; (poly)oxyalkylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan trioleate; (poly)oxyalkylene alkyl (aryl) ether sulfates such as sodium polyoxypropylene methyl ether sulfate and sodium polyoxyethylene dodecylphenol ether sulfate; (poly)oxyalkylene alkyl phosphates such as (poly)oxyethylene stearyl phosphate; (poly)oxyalkylene alkylamines such as polyoxyethylene laurylamine; and polyoxyalkylene amides; the silicone-based defoaming agent is preferably selected from dimethyl silicone oil, silicone paste, silicone emulsion, organically modified polysiloxane (e.g., polyorganosiloxane such as dimethylpolysiloxane), and fluorine-containing silicone oil. The alcohol defoamer is preferably selected from octanol, 2-ethylhexanol, hexadecanol, acetylene alcohol and ethylene glycol; the mineral oil defoamer is preferably selected from kerosene and liquid paraffin. The fatty acid defoamer is preferably selected from oleic acid, stearic acid and its oxyalkylene adduct; the fatty acid ester defoamer is preferably selected from glycerol monoricinoleate, alkenyl succinic acid derivatives, sorbitan monolaurate, sorbitan trioleate and natural wax.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1
[0051] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0052] Raw materials for preparing concrete:
[0053] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0054] Example 2
[0055] 18 g of fluorgypsum, 12 g of disodium dihydrogen pyrophosphate, 12 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0056] Raw materials for preparing concrete:
[0057] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0058] Example 3
[0059] 20 g of fluorgypsum, 8 g of disodium dihydrogen pyrophosphate, 8 g of dolomite, 6 g of monoglyceride, 12 g of calcium sulfoaluminate, 12 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0060] Raw materials for preparing concrete:
[0061] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0062] Example 4
[0063] 18 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 6 g of dolomite, 4 g of monoglyceride, 8 g of calcium sulfoaluminate, 10 g of polyamide and 8 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0064] Raw materials for preparing concrete:
[0065] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0066] Example 5
[0067] 22 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 12 g of calcium sulfoaluminate, 12 g of polyamide and 12 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0068] Raw materials for preparing concrete:
[0069] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0070] Example 6
[0071] 22 g of fluorgypsum, 12 g of disodium dihydrogen pyrophosphate, 12 g of dolomite, 8 g of monoglyceride, 8 g of calcium sulfoaluminate, 8 g of polyamide and 8 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0072] Raw materials for preparing concrete:
[0073] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0074] Example 7
[0075] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0076] Raw materials for preparing concrete:
[0077] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 5kg / m 3 .
[0078] Example 8
[0079] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0080] Raw materials for preparing concrete:
[0081] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.5kg / m 3 .
[0082] Example 9
[0083] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0084] Raw materials for preparing concrete:
[0085] 52.5P·II cement 280kg / m 3 、Fly ash 70kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 40kg / m 3 、River sand 780kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0086] Example 10
[0087] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0088] Raw materials for preparing concrete:
[0089] 52.5P·II cement 290kg / m3 、Fly ash 90kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 32kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1100kg / m 3 , water 135kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0090] Comparative Example 1
[0091] Raw materials for preparing concrete:
[0092] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , expansion agent (purchased from Fujian Yite Building Materials Technology Co., Ltd., trade name: concrete expansion agent) 4.85kg / m 3 .
[0093] Comparative Example 2
[0094] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride, 10 g of calcium sulfoaluminate and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0095] Raw materials for preparing concrete:
[0096] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0097] Comparative Example 3
[0098] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 10 g of calcium sulfoaluminate, 10 g of polyamide and 10 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0099] Raw materials for preparing concrete:
[0100] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0101] Comparative Example 4
[0102] 20 g of fluorgypsum, 10 g of disodium dihydrogen pyrophosphate, 10 g of dolomite, 5 g of monoglyceride and 10 g of calcium sulfoaluminate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain an expansion agent.
[0103] Raw materials for preparing concrete:
[0104] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0105] Comparative Example 5
[0106] 15 g of disodium dihydrogen pyrophosphate, 15 g of dolomite, 10 g of monoglyceride, 10 g of calcium sulfoaluminate, 15 g of polyamide and 15 g of sodium silicate pentahydrate are uniformly mixed and ball-milled to a powder particle size of less than 100 mesh to obtain a swelling agent.
[0107] Raw materials for preparing concrete:
[0108] 52.5P·II cement 290kg / m 3、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 , Prepared expansion agent 4.85kg / m 3 .
[0109] Comparative Example 6
[0110] Raw materials for preparing concrete:
[0111] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , polycarboxylate water reducer 42kg / m 3 , river sand 750kg / m 3 、Crushed stone 1105kg / m 3 , water 130kg / m 3 .
[0112] Experimental example
[0113] The following performance tests were conducted using the concrete provided in Example 1 and Comparative Examples 1 to 6:
[0114] Concrete workability test
[0115] The slump and expansion of concrete are tested according to the method specified in the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T 50080-2016).
[0116] Concrete compressive strength test
[0117] The concrete cube compressive strength test was carried out according to the method specified in the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T 50081-2019). The compressive strength was tested using a cubic specimen with a size of 150mm×150mm×150mm, and the test age was 7d and 28d.
[0118] Concrete shrinkage deformation test
[0119] According to the method specified in the Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), the concrete autogenous shrinkage performance test was carried out. The test was carried out using a YC-BWSD non-contact bellows autogenous shrinkage tester with a bellows size of Φ29×420mm. The autogenous shrinkage rate of the concrete was measured 28 days after final setting.
[0120] The results are shown in Table 1 below:
[0121] Table 1 Test results of concrete performance in each group
[0122]
[0123] It can be seen from the above embodiments that the compound expansive agent provided by the present invention can not only effectively prevent concrete shrinkage, but can even improve the working performance of concrete compared with the original concrete formula without adding the expansive agent, and will not affect the strength of the concrete, thereby achieving a better application effect.
[0124] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite expansion agent, characterized in that: The composition comprises the following components in parts by weight: 18-22 parts of fluorgypsum, 8-12 parts of disodium dihydrogen pyrophosphate, 8-12 parts of dolomite, 3-8 parts of monoglyceride, 8-12 parts of calcium sulfoaluminate, 8-12 parts of polyamide and 8-12 parts of sodium silicate pentahydrate.
2. The composite expansion agent according to claim 1, characterized in that It is composed of the following components in parts by weight: 20 parts of fluorgypsum, 10 parts of disodium dihydrogen pyrophosphate, 10 parts of dolomite, 5 parts of monoglyceride, 10 parts of calcium sulfoaluminate, 10 parts of polyamide and 10 parts of sodium silicate pentahydrate.
3. The method for preparing the composite expansion agent according to claim 1 or 2, characterized in that: The following steps are involved: All raw materials are mixed and ball-milled to obtain the composite expanding agent.
4. The preparation method according to claim 3, characterized in that: The particle size of the composite expansion agent is below 100 meshes.
5. Use of the composite expansive agent according to claim 1 or 2, or the composite expansive agent prepared by the preparation method according to claim 3 or 4 as a concrete additive.
6. The use according to claim 5, characterized in that: The concrete additive is used to prevent concrete from shrinking.
7. The use according to claim 5, characterized in that: The concrete additive is used to improve the working performance and compressive strength of concrete.
8. A concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 250-350 parts of cement, 1500-2500 parts of aggregate, 35-45 parts of anti-cracking agent, 30-50 parts of water reducing agent, and 3-8 parts of the composite expansion agent according to claim 1 or 2.
Citation Information
Patent Citations
Concrete expansion agent
CN104446117A
Concrete expanding agent and preparation method thereof
CN107140864A
Hydration heat inhibition type anti-crack waterproof agent for concrete and preparation method thereof
CN113603385A
Concrete anti-cracking agent, anti-cracking concrete and preparation method of anti-cracking concrete
CN115043610A